ANALISIS MODEL PEMBELAJARAN REFLEKTIF DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH PENDIDIKAN PANCASILA - APRIYANTI WIDIANSYAH (Universitas Bina Sarana Informatika, 2021)
The problems of students show that the values of Pancasila have been eroded in life in society, nation, and state. Therefore, it is necessary to find alternative solutions to various problems, by showing the importance of Pancasila education learning in educational institutions. This is intended to equip students to understand and try to fix some of these problems. In this case, it is necessary to have problem-solving through Pancasila Education learning activities by using the Reflective Learning Model. The research aims to determine the improvement of student learning outcomes in the Pancasila Education course, Faculty of Law, Bhayangkara University, Jakarta Raya. The research was conducted by doing learning actions, and how to make observations. Initial results are expected to bring awareness of students about the importance of Pancasila Education which aims to improve learning outcomes. Furthermore, several preparatory steps are arranged for observing the learning action. Researchers carried out observations of learning in the classroom with a Reflective learning model, by the actions planned in the study. Activities carried out by lecturers who have been provided with observation guidelines by recording all research activities from introduction, development, application, closing and writing additional information that has not occurred such as initiatives and reactions, both from researchers and students, as well as providing conclusions and general suggestions of actions which are conducted. The observation time was adjusted to the Pancasila Education course hours at the Faculty of Law, Bhayangkara University Jakarta Raya